Hospital-based surveillance for rotavirus diarrhea in Ulaanbaatar, Mongolia, April 2009 through March 2016. Issue 51 (14th December 2018) - Samdan, Altanchimeg; Ganbold, Sarangua; Guntev, Oyunchimeg; Orosoo, Solongo; Javzandorj, Narmandakh; Gongor, Amar; Enkhtuvshin, Altansukh; Demberelsuren, Sodbayar; Abdul, Wajid; Jee, Youngmee; Grabovac, Varja; Kirkwood, Carl; et al.
Abstract: Background: Diarrheal disease is one of the leading causes of illness and death in young children in the world, especially the developing countries. Diarrheal disease results in about half a million childhood death per year, ranking second among all causes worldwide. Diarrheal disease due to rotavirus infection is currently the most common cause of severe diarrhea in infants and young children worldwide. Rotavirus immunization of infants is a safe and effective public health intervention for rotavirus infection control and expected to lead to a reduction of childhood morbidity and mortality. Methods: We conducted hospital-based surveillance at two representative hospitals in Mongolia to estimate the burden of hospitalizations for rotavirus diarrhea among children aged <5 years and to describe strain distribution patterns during 6-year study period. Fecal specimens were tested by rotavirus antigen detection enzyme immunoassay (EIA). Specimens that tested positive for rotavirus were further characterized to determine the genotype of strains by reverse-transcriptase polymerase chain reaction. Results: Between April 2009 and March 2016, among 7076 eligible children with diarrhea 6078 patients were enrolled nationally. Forty-six percent (2794/6078) of EIA a specimens were positive for rotavirus. Ninety-three percent (5649/6078) of hospitalizations for diarrhea involved children less than 2 years. No deaths were recorded due to rotavirus diarrhea. The most common genotype was G3P [8] (47.7%) followed by G9P [6] (14.4%), G2P [4] (12%), and G9P [8] (7.1%). Conclusions: This study found a relatively high prevalence of severe rotavirus-associated diarrhea disease in Mongolia and infants were the most affected. It highlights the urgent need for introduction of rotavirus vaccine into the national immunization program. Continued surveillance is crucial and pre-vaccine introduction rotavirus genotype patterns in Mongolia are valuable and can be followed post-introduction to assess vaccine impact.